Network centrality and individual creativity: A mediated moderation of knowledge integration with network cost - Ahmad Adeel; Rizwan Ali; Zhang Pengcheng (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
This study examined peers' perceived central network position with supervisors' rated individual creativity. Employing three sources of data collection technique consist of 286 employees, subordinate-colleague dyads, and their respective 40 supervisors. We collected data from the employees working at controlling offices of a private commercial bank and analyzed proposed hypothesis with hierarchical analysis technique using random coefficient regression with Mplus 7.0. Employees of our sample were working in groups of 6-9 members per workgroup. Overall employees of these work groups represent higher hierarchical level employees of the bank. We examined that, network centrality is related with individual creativity directly and via mediation of knowledge integration; network cost moderated the relationship between network centrality and individual creativity and knowledge integration, however, knowledge integration mediated the relationship between the interaction of network centrality and network cost and individual creativity. Our results revealed that knowledge integration is a consequence of central network positions while network cost negatively affect creativity of centrally positioned employee. Centrally positioned employee can attenuate the negative effects of network cost by integrating knowledge available to him/her due to privileged central network position. We contributed to literature by introducing knowledge integration as a novel predictor of network centrality, network position can have both benefits and costs attached at the same time, and network position holders can enjoy knowledge benefits only when he/she has less network cost.
Keywords: 330; network centrality; knowledge integration; network cost; employee creativity; social capital theory; banking sector